2015
DOI: 10.1038/srep07696
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13-positive mast cells are increased in immunoglobulin G4-related sialadenitis

Abstract: Interleukin (IL)-13 is a T helper 2 (Th2) cytokine that plays important roles in the pathogenesis of asthma. IL-13 induces hypersensitivity of the airways, increased mucous production, elevated serum immunoglobulin (Ig) E levels, and increased numbers of eosinophils. Many patients with IgG4-related disease have allergic backgrounds and show elevated serum IgE levels and an increase in the number of eosinophils. Upregulation of Th2/regulatory T (Treg) cytokines, including IL-13, has been detected in affected ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…In contrast to pre-treatment renal function, the impact of serum IgE elevation on renal prognosis has not thus far been documented in IgG4-RKD. Concerning the pathophysiology of IgG4-RD, however, upregulation of T helper (Th) 2 cytokines including interleukin (IL)-4 and IL-13, which promote IgE production, in the affected lesions have been reported [2629]. Furthermore, it has been indicated that such Th2 cytokines, especially IL-13, play a dominant role in the fibrosis observed in Th2-upregulated conditions [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to pre-treatment renal function, the impact of serum IgE elevation on renal prognosis has not thus far been documented in IgG4-RKD. Concerning the pathophysiology of IgG4-RD, however, upregulation of T helper (Th) 2 cytokines including interleukin (IL)-4 and IL-13, which promote IgE production, in the affected lesions have been reported [2629]. Furthermore, it has been indicated that such Th2 cytokines, especially IL-13, play a dominant role in the fibrosis observed in Th2-upregulated conditions [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…For cytokine detection, previous studies used quantitative real-time PCR with RNA extracted from frozen tissue of affected organs or fluorescent dual immunohistochemical analysis of frozen tissue samples. [6][7][8][9] However, when endovascular aortic replacement for AAA became popular, obtaining new frozen samples of IgG4-AAs for estimates became difficult. Our study depended on data from formalin-fixed, paraffin-embedded slides stored for 1 to 8 years.…”
Section: Serum Il-10 and Il-13 Levels Were Rather High Inmentioning
confidence: 99%
“…1 Two recent reports have shed new light on increased mast cell infiltration in IgG4-related sialadenitis. 7,8 In response to IgE stimulation, mast cells secrete various mediators, including IL-6. 37 A recent report on cutaneous IgG4-RD found that IC IL-6 mark the 75th and 25th percentiles, respectively, and the whiskers above and below the box extend 1.5 interquartile range in either direction.…”
Section: Serum Il-10 and Il-13 Levels Were Rather High Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-localization analyses on cells expressing both GATA3 and IL-4, IL-5, or IL-13 have not been performed in the lesions of IgG4-RD patients. Therefore, it is possible that IL-4 and IL-13 may be derived from other types of cells, such as T follicular helper (Tfh) cells (Akiyama et al 2015;Maehara et al 2012;Moriyama et al 2014) and mast cells (Takeuchi et al 2014(Takeuchi et al , 2015 rather than conventional TH2 cells.…”
Section: Igg4-rd and T Helper Type 2 Cytokinesmentioning
confidence: 99%